Appeared inexplicable disorders of consciousness after general anesthesia tracheal tube drawing in endoscopic tympanoplasty. Issue 2 (28th June 2021) - Qian, Kun; Cao, Song; Liu, Xing‐Kui
Abstract : Background: Disorders of consciousness (DOC) are neurocognitive disorders related to sharp fluctuations of attention and consciousness, while DOC is characterized by significant interindividual differences, rapid development, and a higher lethal rate. Case information: A 53‐year‐old female patient underwent general anesthesia with tracheal intubation in otoendoscopic tympanoplasty. The patient suddenly appeared moderate DOC after tracheal tube removal with K + 3.6 (3.5–5.3 mmol/L). Based on the ancillary testing and routine laboratory workup, the possible causes of DOC, such as general anesthesia drugs and cardio cerebral events, were temporarily excluded. DOC was reversed by intravenous administration of KCl 1 g, with K + 3.78 mmol/L. On one day after surgery, the patient occurred suddenly DOC again after intravenous guttae of 5% glucose 1000 ml, K + 3.87 mmol/L, possibly because of her recurrent hypokalemic paralysis (HP) of past medical history. The patient's consciousness gradually improved after effective KCl supplementation therapy. Conclusion: DOC caused by periodic paralysis (PP) has not been reported, we speculate that hypoactive DOC is closely correlated with normokalemic periodic paralysis (NormoPP) in this case.